2019
DOI: 10.1016/j.celrep.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Aryl Hydrocarbon Receptor Interacting Protein Maintains Germinal Center B Cells through Suppression of BCL6 Degradation

Abstract: Summary B cell lymphoma-6 (BCL6) is highly expressed in germinal center B cells, but how its expression is maintained is still not completely clear. Aryl hydrocarbon receptor interacting protein (AIP) is a co-chaperone of heat shock protein 90. Deletion of Aip in B cells decreased BCL6 expression, reducing germinal center B cells and diminishing adaptive immune responses. AIP was required for optimal AKT signaling in response to B cell receptor stimulation, and AIP protected B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…Increased GH release has been found in AIP-disrupted cells, probably associated with the increased STAT3 phosphorylation ( 41 , 46 ), while an altered microenvironment may also explain the aggressive phenotype of some of these tumors ( 47 ). However, the role of other AIP partners—nuclear receptors (AHR, ER, GR, PPRα, TRβ1), mitochondrial proteins, survivin (reviewed in ( 48 )) or BCL6 ( 49 ) in the pituitary-specific effects is unclear.…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Increased GH release has been found in AIP-disrupted cells, probably associated with the increased STAT3 phosphorylation ( 41 , 46 ), while an altered microenvironment may also explain the aggressive phenotype of some of these tumors ( 47 ). However, the role of other AIP partners—nuclear receptors (AHR, ER, GR, PPRα, TRβ1), mitochondrial proteins, survivin (reviewed in ( 48 )) or BCL6 ( 49 ) in the pituitary-specific effects is unclear.…”
Section: Genetic Mechanisms Of Tumorigenesismentioning
confidence: 99%
“…Being a chaperone, not surprisingly several novel interacting proteins have been described for AIP [ 17 ] and miR34 has also emerged in two independent studies as a related key microRNA [ 18 , 19 ]. Knowledge derived from cell-based experiments considers AIP as a tumour suppressor in some cell types [ 7 , 8 , 15 ], but not all [ 20 ]. Global knockout in mice, Drosophila and C. elegans shows embryonic lethality [ 21 – 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…Data from studies screening all human organs confirmed AIP mRNA expression in 36 studied tissues ( 37 ). We have recently identified a role of AIP in lymphocytes, which could be a source of circulating AIP ( 38 ). A close correlation between AIP and GH levels may not be expected due to their highly discrepant half-lives, being in the order of 30 h for AIP compared to only 16 min for GH ( 10 ).…”
Section: Discussionmentioning
confidence: 99%